Los operadores de comercio exterior: la nueva propuesta de la Ley General de Aduanas - Caballero Caballero, Javier Alonso (2021)
The new decade offers great possibilities of success for international commerce-related companies, whose quality and efficiency sets them apart from the competition. International commerce requires reducing timeframes and costs, all of this within an agile, legal and safe commerce. It is important to know the mechanisms that offer competitive advantages to this end.